Analisis Kelayakan dan Strategi Bisnis Gula Aren Premium Gunung Halimun-Salak - Hartonoadi Wahyudi; Jimmy Jimmy; Kendy Leyona Artha; Prasetyo Adi Yudhistira; Wahyu Seto (Universitas Prasetiya Mulya, 2019)
The research purpose is to identify the feasibility of premium arenga sugar originated from Conservative Forest of HalimunSalak. This Business is based on the social issue that occurs in the community due to sales decrease of arenga sugar as the main source of income. This research is also intended as based for strategy related to marketing, operation, human resource, and finance. The research methods are direct observations, expert interviews, taste panels, dan focus group. With the IDR 16 bio, this business resulted in NPV more than 0 (Rp 36.233.793.890), IRR (45%) bigger than WACC (12%), and Payback period 3,5 years. These results exceed the shareholder's expectation so that the business is worth to be realized.